Jews and their Roman rivals: pagan Rome's challenge to Israel - Berthelot, Katell (Princeton University Press, 2021)
How encounters with the Roman Empire compelled the Jews of antiquity to rethink their conceptions of Israel and the TorahThroughout their history, Jews have lived under a succession of imperial powers, from Assyria and Babylonia to Persia and the Hellenistic kingdoms. Jews and Their Roman Rivals shows how the Roman Empire posed a unique challenge to Jewish thinkers such as Philo, Josephus, and the Palestinian rabbis, who both resisted and internalized Roman standards and imperial ideology.Katell Berthelot traces how, long before the empire became Christian, Jews came to perceive Israel and Rome as rivals competing for supremacy. Both considered their laws to be the most perfect ever written, and both believed they were a most pious people who had been entrusted with a divine mission to bring order and peace to the world. Berthelot argues that the rabbinic identification of Rome with Esau, Israel's twin brother, reflected this sense of rivalry. She discusses how this challenge transformed ancient Jewish ideas about military power and the use of force, law and jurisdiction, and membership in the people of Israel. Berthelot argues that Jewish thinkers imitated the Romans in some cases and proposed competing models in others.Shedding new light on Jewish thought in antiquity, Jews and Their Roman Rivals reveals how Jewish encounters with pagan Rome gave rise to crucial evolutions in the ways Jews conceptualized the Torah and conversion to Judaism